2011
DOI: 10.1021/ja201181g
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Methylenetetrahydrofurans by Palladium-Catalyzed [3 + 2] Cycloaddition of Trimethylenemethane with Aldehydes – A Novel Ligand Design

Abstract: The palladium-catalyzed [3+2] cycloaddition of trimethylenemethane (TMM) with aldehydes is a direct and efficient route to methylenetetrahydrofurans. Herein we describe the first asymmetric synthesis of methylenetetrahydrofurans utilizing a palladium-TMM complex in the presence of a novel phosphoramidite ligand possessing a stereogenic phophorus. The method allows for the formation of chiral disubstituted tetrahydrofurans in good yields and enantioselectivies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…3a Using these ligands, we have demonstrated asymmetric [3+2] cycloadditions with several olefins, 3 imines 4 and aldehydes. 5 …”
mentioning
confidence: 99%
“…3a Using these ligands, we have demonstrated asymmetric [3+2] cycloadditions with several olefins, 3 imines 4 and aldehydes. 5 …”
mentioning
confidence: 99%
“…Because the BINOL derivative in L1 is unsymmetric, the ligand is chiral at phosphorus (R P and S P ). In our previous work, [4] we found that only a single diastereomer of L1 was active. Thus, the chirality at phosphorus serves as a unique control element for the reactivity of the catalyst, a phenomenon which to the best of our knowledge has not been previously described in the chemical literature.…”
mentioning
confidence: 74%
“…Among the many approaches towards their synthesis, [1] cycloaddition represents a powerful and attractive strategy, [2] but catalytic enantioselective variants remain rare. [3,4] We recently disclosed one such approach involving the palladium-catalyzed cycloaddition of trimethylenemethane (TMM) with aldehydes. [4c] Herein, we describe the surprising success of this method in reactions with aromatic ketones, a substrate class which was previously unknown in Pd/TMM reactions using achiral ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Trost and co-workers coupled trimethylenemethane with aromatic aldehydes and ketones in a palladium catalyzed process leading to methylene tetrahydrofuran structures in good yield (Scheme 59). 209,210 Excellent enantioselectivity could be obtained using chiral phosphoramidite ligands. Other possible 1,3-dipole equivalents are 3-chloropropylphenylsulfones or sulfoxides, activated by a Brønsted base, used by the group of Mąkosza to form trans-2,3 disubstituted oxolanes.…”
Section: Other Annulation Reactionsmentioning
confidence: 99%